Tratamento conjugado de lixiviado de aterro sanitário e esgoto doméstico por processo anaeróbio seguido de aeróbio - Silva, Risoneide Borges da (2014)
The landfill leachate has a high level of pollution, as it has high levels of ammonia and organic compounds that cause environmental impacts if released untreated into receiving bodies. One of the alternatives that may be feasible and effective for the treatment of leachate treatment is conjugate Sanitary landfill leachate using more domestic wastewater biological treatment systems. Given the above the present research work aims to investigate the treatment process combined landfill leachate and domestic sewage in UASB reactor followed by aerobic trickling filter bed. The experimental system was designed, built and monitored the physical premises of the Experiment Station Biological Treatment of Sewage (EXTRABES), State University of Paraiba, Campina Grande - PB, Brazil, constituting a UASB reactor and an aerobic trickling filter bed. The substrate used in the treatment, to supply the reactors was prepared daily and consisted of mixing 99% of domestic sewage plus 1% of landfill leachate (volume percent). The operation of the experimental system was divided into two phases, the first lasting six months and the second four months. The results showed that the average concentration of the final effluent BOD of 90 mg / L and an average removal efficiency of the system by 63% in the first stage, the second stage the average removal efficiency was 77% with an average concentration of effluent end of 51 mg / L. The average removal efficiencies of COD Total 5 and N-NH 4 + in the system was 85% and 21% respectively in step 1 and 89% and 61% in the second stage. The nitrate concentration in the effluent of aeróbiopercolador filter in the first step with an average value was less than 7.6 mg / L in the second stage, average 36mg / L, which was higher nitrification. Based on the results obtained it follows that the conjugate treatment of landfill leachate over sewage constitutes an efficient and viable alternative for the treatment of leachate by favoring their treatment by biological process. It was further observed that for pH indicators and BOD5 mean values of the final effluent are within standard conditions established by CONAMA 430/2011, for disposal in water bodies and Ammoniacal Nitrogen averaged near the standard set by this standard, and the minimum values reached 18 mgN-NH 4 + L.